Study on Dimensionless Mid-tower Stiffness of Three-Tower Self-Anchored Suspension Bridges Based on an Analytical Approach. (November 2022) - Liu, Shuang; Cao, Hongyou; Chen, Zhijun; Habib, Muhammad; Zhu, Hongping
Abstract: Different from the earth-anchored suspension bridges, both the main cable and the stiffening girder significantly contribute to the stiffness of self-anchored suspension bridges. Meanwhile, the mid-tower effect is also non-negligible when extending the traditional self-anchored suspension bridges to the multi-tower system. This study derives a load distribution coefficient to include the coupling effect between the main cable and girder based on displacement compatibility conditions. The load distribution coefficient determines the live-load deflection of the girder and the cable forces on both sides of the mid-tower, corresponding to the lower and upper bound of the mid-tower stiffness. This study also proposed an analytical approach to determine the feasible dimensionless range of the mid-tower stiffness for three-tower self-anchored suspension bridges. The nonlinear finite element method is utilized to validate the accuracy of the analytical model, and a parametric analysis is carried out to examine the effects of different parameters, including the live-load ratio suffered by the main cable, the geometric and loading parameters, the cable-girder connections, and the tower-girder connections, on the range of dimensionless mid-tower stiffness. The results demonstrate that the feasible stiffness range of mid-tower depends on more parameters, including the live-load ratio supported by the main cable, the dead-to-live load ratio, the sag-to-span ratio, and the cable-girder connections, compared with three-tower earth-anchored suspension bridges.